USOS E APROPRIAÇÕES DE PRÁTICAS EDUCOMUNICATIVAS EM SITUAÇÕES DE ENSINO E APRENDIZAGEM - Oliveira, Cristiano de Souza (2021)
The aim of this study was to investigate the educommunicative practices studied in the Master's Course in Teaching Humanities and Languages at UFN (Universidade Franciscana) that reflect on the actions of the students in their teaching practices in the form of using their tools in situations of teaching and learning and the guiding question of the research was: Does the understanding of Educommunication, its practices and processes influence the use of teaching and learning spaces through more communicative procedures? For this approach, it was taken into account that Educommunication is a field of study that proposes a reflection on the mediation of communication and the media in the most diverse teaching and learning processes, proposing a collaborative learning, supported mainly by the communication processes through the educommunicative tools, technologies, where everyone has to teach and everyone has to learn and in this process communication is seen as a transversal axis and needs to be present socializing models to understand the world. This research has a qualitative approach and the corpus of analysis included students from the Master in Teaching Humanities and Languages, who act as teachers and who studied the subject of Educommunication. In view of the listed objectives, data collection was used in the research through a questionnaire applied to students who met the requirements of the corpus. For data analysis, we follow Bardin's guidance for content analysis with critical and reflective interpretation. And among all the results it was concluded that the educommunicative practices studied in the Master's course in Teaching Humanities and Languages are reflected in the actions of the students in their teaching practices in the form of using their tools in teaching and learning situations.